An improved low complexity Near Lossless Image Compression. (3rd January 2012) - Gupta, Mohit Kumar; Londhe, Narendra D.
In this paper, a new improved low complexity compression methodology named as Near Lossless Image Compression (NLIC) has been suggested. This algorithm is a hybrid method which includes DCT, a lossy compression technique and JPEG encoding using entropy based Huffman coding, a lossless compression technique. The algorithm is tested with standard square images of sizes 512 × 512 and 1024 × 1024 respectively. The results of NLIC are also compared with the Huffman and Run length Encoding (RLE) for evaluating its compression efficiency.